Dynamics of Infatuation Trends in Indonesia: Between Forgiveness and Divorce from the Perspective of Maqashid al-Usrah - Yurika Anidza Faqih; Ahmad Wildan Rofrofil Akmal (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
A common issue in Indonesian divorces is infidelity, as evidenced by the frequent circulation of divorce news on social media. Infidelity has become a prevalent trend, particularly within families, influenced by various factors, including the advancement of increasingly sophisticated technology. Moreover, the problem of infidelity remains contentious, with assumptions and arguments that sometimes justify condoning infidelity or even endorsing divorce. This study explores why infidelity has emerged as a significant socio-religious issue in contemporary Muslim family discourse. The analysis interprets infidelity and examines responses such as forgiveness and divorce through the lens of Jamaluddin Athiyyah's Maqashid al-Usrah framework. The research employs normative legal methods, library research, and document analysis. The findings suggest the necessity of strengthening Islamic family ethics, focusing on protecting dignity, ensuring relational justice, and preventing broader socio-religious harm.